THE SYSTEM OF AGREEMENTS FOR DISTRIBUTION OF GOODS WITH MANUFACTURING COMPANIES AND ITS IMPLEMENTATION ACCORDING TO THE CONCEPT OF BAI ISTISNA’ - Khalilur Rahman; Armiadi Musa (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
Contracts are fundamental in commercial activities, including cooperation between businesses and manufacturers in ordering goods. This study aims to examine the system of agreements for ordering goods between Distro Mens Surfing Banda Aceh and garment manufacturers, analyze the implementation of these agreements, and assess their compatibility with the concept of Bai Istisna’ contracts according to commercial fiqh. This study uses a qualitative method with a normative empirical approach, through interviews and documentation as data collection techniques. The results show that goods ordering agreements are made verbally and digitally. Still, the production of goods often does not meet the agreed specifications regarding color, material, and stitching quality. Other findings indicate that this condition causes losses for the purchaser of the goods due to the absence of a return mechanism, which shows that the principle of khiyar' aibi, namely the buyer's right to cancel the contract or request compensation if the goods received are defective or do not meet the specifications, is not applied. The absence of the application of khiyar' aibi places the purchaser of the goods in a disadvantaged position and causes injustice in the transaction. Conceptually, this transaction has fulfilled the Bai Istisna’ elements in ordering based on specifications and installment payments. Still, it does not fully reflect the principle of balance between rights and responsibilities in Islamic muamalah.